The moral leader challenges, insights, and tools - Sucher, Sandra J. (Routledge, 2008)
Aims to help students wrestle with the definition of moral leadership. This book allows students to ponder moral challenges. It emphasizes decision-making and action, guiding the student reader through the theories of moral leadership as well as enabling a journey of discovery.